Biomineralized Metal–Organic Framework Nanoparticles Enable Intracellular Delivery and Endo-Lysosomal Release of Native Active Proteins - Chen, Ting-Ting; Yi, Jin-Tao; Zhao, Yan-Yan; Chu, Xia (Journal of the American Chemical Society, 2018)
Efficient delivery and endo-lysosomal release of active proteins in living cells remain a challenge in protein-based theranostics. We report a novel protein delivery platform using protein-encapsulating biomineralized metal–organic framework (MOF) nanoparticles (NPs). This platform introduces an adapted biomimetic mineralization method for facile synthesis of MOF NPs with high protein encapsulation efficiency and a new polymer coating strategy to confer the NPs with long-term stability. In vitro results show that protein-encapsulating MOF NPs have the advantages of preserving protein activity for months and protecting proteins from enzyme-mediated degradation. Live cell studies reveal that MOF NPs enable rapid cellular uptake, efficient release and escape of proteins from endo-lysosomes, and preservation of protein activity in living cells. Moreover, the developed platform is demonstrated to enable easy encapsulation of multiple proteins in single MOF NPs for efficient protein co-delivery. To our knowledge, it is the first time that protein-encapsulating MOF NPs have been developed as a generally applicable strategy for intracellular delivery of native active proteins. The developed protein-encapsulating biomineralized MOF NPs can provide a valuable platform for protein-based theranostic applications.